Hubungan Self Efficacy Dengan Sikap Belajar Siswa Sekolah Menengah Kejuruan Negeri 2 Pekanbaru - Desi Wulandari; Amirah Diniaty (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2020)
This research aimed to know (1) students’ self-efficacy, (2) students’ learning attitude, and (3) the correlation between students’ self-efficacy and their learning attitude.  It was a correlational research. The population was all of the students of eleventh grade state  that were 320 students. While, The sample of this research was 80 students. Questionnaire and documentation were the techniques of collecting the data. The data was analyzed statistically by using Product Moment correlation technique. The result showed that (1) students’ self-efficacy at the eleventh grade of  was on high category, it was based on the percentage of questionnaire answer 83.93% and it was very good, (2) their learning attitude at the eleventh grade of State Vocational High School 2 Pekanbaru was on good category, it was based on the percentage of questionnaire answer 80.76% and it was very good, (3) there was a significant correlation between students’ self-efficacy and their learning attitude at the eleventh grade of State Vocational High School 2 Pekanbaru, it could be seen from the product moment correlation score 0.656, and this score was higher than rtable 0.227.